2013
DOI: 10.1002/humu.22470
|View full text |Cite
|
Sign up to set email alerts
|

A HomozygousPDE6DMutation in Joubert Syndrome Impairs Targeting of Farnesylated INPP5E Protein to the Primary Cilium

Abstract: Joubert syndrome (JS) is characterized by a distinctive cerebellar structural defect, namely the « molar tooth sign ». JS is genetically heterogeneous, involving 18 genes identified to date, which are all required for cilia biogenesis and/or function. In a consanguineous family with JS associated with optic nerve coloboma, kidney hypoplasia and polydactyly, combined exome sequencing and mapping identified a homozygous splice site mutation in PDE6D, encoding a prenyl-binding protein. We found that pde6d depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 32 publications
4
124
1
Order By: Relevance
“…Interestingly, another recent study showed that MO depletion of PDE6D, one of several genes mutated in Joubert syndrome, also causes pronephric cysts. 26 The large size of the PDE family makes the rapid dissection in zebrafish an attractive way to explore the significance of family members. Although it is not clear whether PDE1A will prove to be among the more potent PDEs regulating cystogenesis, it is worth noting that depletion of PDE1A alone was sufficient to induce cysts.…”
Section: Camentioning
confidence: 99%
“…Interestingly, another recent study showed that MO depletion of PDE6D, one of several genes mutated in Joubert syndrome, also causes pronephric cysts. 26 The large size of the PDE family makes the rapid dissection in zebrafish an attractive way to explore the significance of family members. Although it is not clear whether PDE1A will prove to be among the more potent PDEs regulating cystogenesis, it is worth noting that depletion of PDE1A alone was sufficient to induce cysts.…”
Section: Camentioning
confidence: 99%
“…INPP5E showed an approximately 100 fold higher binding affinity to PDE6d with a dissociation constant in the nanomolar range as compared to submicromolar affinities for Ras and Rheb. 46 Stimulated by the findings that only Arl3 can release high affinity ciliary cargo from Unc119 12,15 and from PDE6d, 38 we could confirm that under identical concentrations only Arl3 is able to release a C-terminal prenylated INPP5E peptide from its complex with PDE6d, while Arl2 did not. 46 Kinetic studies showed that the stimulated release of farnesylated INPP5E peptide by Arl3 GTP is 600fold faster than by Arl2 GTP.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 58%
“…This was indeed verified by a number of biochemical and cellular studies which suggested that PDE6d is a general prenyl binding protein (therefore also called PrBP) without apparent selectivity. [33][34][35][36][37][38][39] In contrast to RhoGDI and RabGDI which are specific for the GDP-bound conformation of prenylated Rho or Rab proteins, 39,40 PDE6d binds Ras and Rheb independent of their nucleotidebound conformation. 34,41 The structure of the Arl2-PDE6d complex shows however that the hydrophobic pocket is partially occupied suggesting a mutually exclusive binding to prenylated cargo and/or Arl2.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%
“…This idea is supported by the observation that mutations in PDE6D produce mice with renal, ocular, and neurological defects reminiscent of defects observed in INPP5E deficient mice. 87 As indicated earlier, binding to PDE6D is required for its PC localization, 86 and the mutated Inpp5E MORM variant is unable to sustain interaction with PDE6D and therefore, is unable to localize in the PC. 87 As a whole, these results indicate that Inpp5E-mediated ciliary stability requires both proper localization to the cilium as well as a fully functional phosphatase.…”
mentioning
confidence: 83%
“…86 Indeed, absence of PDE6D was linked to Inpp5E mislocalization and to Joubert syndrome. 87 PDE6D binding to prenylated proteins is known to be regulated by the ARF-like proteins Arl2 and Arl3; however, whether Arl2/3 or Arl13, directly or indirectly control the formation of a PDE6D-Inpp5E-targeted complex needs to be further clarified.…”
Section: Inositol Polyphosphate-5′ Phosphatase E: Inpp5ementioning
confidence: 99%